The ‘three-legged stool’: a system for spinal informed consent - Powell, J. M.; Rai, A.; Foy, M.; Casey, A.; Dabke, H.; Gibson, A.; Hutton, M. (The bone & joint journal, 2016)
Many hospitals do not have a structured process of consent, the attainment of which can often be rather ‘last-minute’ and somewhat chaotic. This is a surprising state of affairs as spinal surgery is a high-risk surgical specialty with potential for expensive litigation claims. More recently, the Montgomery ruling by the United Kingdom Supreme Court has placed the subject of informed consent into the spotlight. There is a paucity of practical guidance on how a consent process can be achieved in a busy clinical setting. The British Association of Spinal Surgeons (BASS) has convened a working party to address this need. To our knowledge this is the first example of a national professional body, representing a single surgical specialty, taking such a fundamental initiative. In a hard-pressed clinical environment, the ability to achieve admission reliably on the day of surgery, in patients at ease with their situation and with little likelihood of late cancellation, will be of great benefit. It will reduce litigation and improve the patient experience. Cite this article: Bone Joint J 2016;98-B:1427–30.